2015
DOI: 10.1038/pr.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 confers protection and alters T-cell populations in a mouse model of neonatal intestinal inflammation

Abstract: Background: Necrotizing enterocolitis (NEC), an intestinal inflammatory disease affecting premature infants, is associated with low regulatory T (Treg) to effector T (Teff ) cell ratios. We recently demonstrated that heme oxygenase-1 (HO-1) deficiency leads to increased NEC development. Here, we investigated the effects of HO-1 on T-cell proportions in a murine NEC-like injury model. Methods: Intestinal injury was induced in 7-d-old wildtype (WT) or HO-1 heterozygous (HO-1 Het) pups by formulafeeding every 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…Similar observations were made in mouse models for inflammatory diseases, such as in lactobacillus‐mediated infection where HO‐1 activity was required to efficiently produce mesenteric Foxp3 + CD25 + CD4 + T cells . Moreover, transfer of wild‐type regulatory T cells into HO‐1 heterozygous mice restored the ratios between regulatory and effector T cells and reduced inflammation in a model of necrotizing enterocolitis, supporting a possible direct role for HO‐1 in the generation and function of regulatory T cells . Hence, the HO‐1–CO system arises as a powerful candidate to restrict antigen presentation to T cells in vivo and also to impair the activation of lymphocytes in transplantation and autoimmunity.…”
Section: The Ho‐1–co System Reduces Pathologies Caused By the Immune supporting
confidence: 59%
See 1 more Smart Citation
“…Similar observations were made in mouse models for inflammatory diseases, such as in lactobacillus‐mediated infection where HO‐1 activity was required to efficiently produce mesenteric Foxp3 + CD25 + CD4 + T cells . Moreover, transfer of wild‐type regulatory T cells into HO‐1 heterozygous mice restored the ratios between regulatory and effector T cells and reduced inflammation in a model of necrotizing enterocolitis, supporting a possible direct role for HO‐1 in the generation and function of regulatory T cells . Hence, the HO‐1–CO system arises as a powerful candidate to restrict antigen presentation to T cells in vivo and also to impair the activation of lymphocytes in transplantation and autoimmunity.…”
Section: The Ho‐1–co System Reduces Pathologies Caused By the Immune supporting
confidence: 59%
“…125 Moreover, transfer of wild-type regulatory T cells into HO-1 heterozygous mice restored the ratios between regulatory and effector T cells and reduced inflammation in a model of necrotizing enterocolitis, supporting a possible direct role for HO-1 in the generation and function of regulatory T cells. 126 Hence, the HO-1-CO system arises as a powerful candidate to restrict antigen presentation to T cells in vivo and also to impair the activation of lymphocytes in transplantation and autoimmunity. Furthermore, the generation of regulatory T cells during bacteria-dependent inflammation and graft acceptance seems to depend on the HO-1 activity.…”
Section: Ho-1 Reduces Innate Immunity-mediated Inflammatory Diseasesmentioning
confidence: 99%
“…Although the pathogenesis of cholestasis associated with severe hemolysis was not our focus, our findings support the notion that there are several existing physiologic systems (HO, heme/hemoglobin-binding proteins, hemopexin [19], albumin, and haptoglobin [5]) available to attend to the potential toxicity of FH. Deficiencies among any of those systems should be evaluated when considering the role of HO deficiency in the pathogenesis of various oxidative injuries in the neonate [17,20,21]. Our data affirm differences between newborn and adult mice with respect to HO activity at baseline and after exposure to FH or MHA.…”
Section: Discussionsupporting
confidence: 67%
“…One- and 5-week-old wild-type (Wt) FVB and HO-1 heterozygous (Het, HO-1 +/- ) mice were used [16,17]. One-week-old mice were kept with their mothers until sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, heme directly regulates various molecular and cellular processes, has been shown to act as a Tcell mitogen in vitro (39) and exerts mild proinflammatory responses encompassing the activation of macrophages and polymorphonuclear cells (40)(41)(42). Furthermore, recent findings have shown that oral administration of heme prior to induction of necrotizing enterocolitis decreased disease incidence and increased Treg/Teff ratios (43). In addition, Konrad and collaborators (44) demonstrated that topical administration of hemin was protective against pulmonary inflammation.…”
Section: Discussionmentioning
confidence: 99%